2008
DOI: 10.1161/hypertensionaha.107.096297
|View full text |Cite
|
Sign up to set email alerts
|

α 2 -Adrenoceptors Enhance Angiotensin II–Induced Renal Vasoconstriction

Abstract: Abstract-␣ 2 -Adrenoceptors potentiate renal vascular responses to angiotensin II via coincident signaling at phospholipase C. This leads to increased activation of the phospholipase C/protein kinase C/c-src pathway. Studies suggest that c-src activates the reduced nicotinamide-adenine dinucleotide phosphate (NADPH) oxidase/superoxide system, and reactive oxygen species stimulate the RhoA/Rho kinase pathway. Therefore, we hypothesized that NADPH oxidase/superoxide and RhoA/Rho kinase are downstream components … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…Losartan or apocynin reduces ROS content and ameliorates the low responses of blood vessel to vasoconstrictor in the mesenteric artery in rats induced by bile duct ligation 10. Recent studies have reported that ROS can affect the function of ROCK in vascular smooth muscles in vascular diseases such as pulmonary hypertension 11, hypertension 12,13 and cerebrovascular disease 14. Therefore, we speculate that ROS may be participated in the regulation of ROCK in vascular smooth muscle.…”
Section: Introductionmentioning
confidence: 82%
“…Losartan or apocynin reduces ROS content and ameliorates the low responses of blood vessel to vasoconstrictor in the mesenteric artery in rats induced by bile duct ligation 10. Recent studies have reported that ROS can affect the function of ROCK in vascular smooth muscles in vascular diseases such as pulmonary hypertension 11, hypertension 12,13 and cerebrovascular disease 14. Therefore, we speculate that ROS may be participated in the regulation of ROCK in vascular smooth muscle.…”
Section: Introductionmentioning
confidence: 82%
“…The effect of CS on the RhoA-Rho kinase pathway also appears to be systemic, because CS exposure activates Rho kinase in the forearm vasculature of human subjects, leading to a higher degree of vasoreactivity (71). More broadly, reactive oxidant species activate the RhoA-Rho kinase pathway in several settings, both in an NADPH oxidasedependent and -independent manner (34,69,(72)(73)(74); but the converse has also been observed, that reactive oxygen species may down-regulate RhoA activity (75). So reactive oxygen species may retain the ability to activate or deactivate Rho GTPases, depending on the context.…”
Section: Discussionmentioning
confidence: 99%
“…First, basal perfusion pressures are lower than arterial pressure because the kidneys are perfused with Tyrode's solution, which has much lower viscosity compared with blood (2). Despite this, the isolated, perfused rat kidney is characterized by high vascular sensitivity to vasoconstrictors (17,36,51) and the vascular response of the preparation is similar to that observed in vivo (34). Second, Tyrode's solution is a poor oxygen carrier.…”
Section: F472mentioning
confidence: 99%